If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -1(x + -3) + 6(x + -2) Reorder the terms: -4 = -1(-3 + x) + 6(x + -2) -4 = (-3 * -1 + x * -1) + 6(x + -2) -4 = (3 + -1x) + 6(x + -2) Reorder the terms: -4 = 3 + -1x + 6(-2 + x) -4 = 3 + -1x + (-2 * 6 + x * 6) -4 = 3 + -1x + (-12 + 6x) Reorder the terms: -4 = 3 + -12 + -1x + 6x Combine like terms: 3 + -12 = -9 -4 = -9 + -1x + 6x Combine like terms: -1x + 6x = 5x -4 = -9 + 5x Solving -4 = -9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + -5x = -9 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + -5x = -9 + 0 -4 + -5x = -9 Add '4' to each side of the equation. -4 + 4 + -5x = -9 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = -9 + 4 -5x = -9 + 4 Combine like terms: -9 + 4 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 5(c-8-3)-3(2c+12)=-84 | | 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 | | 5x+1-7=-1 | | 25+37-2x=11 |